ANALISIS PENGETAHUAN, SIKAP DAN PERILAKU IBU BALITA GIZI BURUK DAN KURANG DI WILAYAH KERJA PUSKESMAS OESAPA KOTA KUPANG PROPINSI NUSA TENGGARA TIMUR - Yohanes Don Bosko Demu (Jurnal GIZIDO, 2017)
At the moment there are an estimated 38.4 million Indonesians living below the poverty line. More than 5 million children under the age of five suffer from malnutrition and about 100 million people are at risk from other nutritional problems (less iron, less iodine, less vitamin A, less calcium, less zinc, etc. Weight is the first indicator that can be seen when a person is malnourished.In the long term, malnutrition will lead to high growth barriers and ultimately adversely affect the individual's mental-intellectual development Objective: Identify Knowledge, Attitudes and Behavior of Underfive Malnourished and Underweight Children in the Working Area Puskesmas Oesapa Kota Kupang, East Nusa Tenggara Province. Method: This research was conducted by observational method with cross-sectional approach. Population in this research all mother of balita who have child malnutrition and less become respondent in working area of puskesmas Oesapa City of Kupang which amounted to 30 respondents. Sampling technique in total sampling. Results: Most respondents in this study were 20-35 years old (74.2%). Most of the respondents had an elementary education (38.7%), worked as housewives (IRT) 96.8%, most had more than 4 (54.8%) family members, had less than minimum wage province (87.1%). Based on maternal nutrition knowledge indicator is known that most have good knowledge of nutrition (96,8%), based on indicator of nutrition attitude known most of respondents have good nutrition attitude (90,3%) and based on indicator of nutritional behavior known that mother's nutritional behavior mostly categorized as good (74.2%). Conclusion: Most of the respondents in this study were 20-35 years old. An elementary school, working as a housewife (IRT), has a family member of more than 4 people, has an income less than the provincial minimum wage. Most have good nutritional knowledge, have good nutritional attitudes, and mother's nutritional behavior is largely categorized well.